Balancing Independence and Accountability: Reforming Prosecutorial Immunity in Indonesia’s Legal System - zuraidah, Zuraidah; Setiadi, Edi; Rohaeni, Neni; Ismail, Noorfajri (Universitas Muhammadiyah Purwokerto, 2026)
This research examines the juridical implications of Article 8 paragraph (5) of Law Number 11 of 2021 concerning the Indonesian Attorney General’s Office, which stipulates that any legal action against prosecutors such as summons, detention, search, and interrogation must be approved by the Attorney General. While the provision was originally intended to safeguard institutional independence, its application has raised serious concerns regarding the erosion of the equality before the law principle and the emergence of internal impunity mechanisms. Using a normative juridical approach combined with statutory, conceptual, and case study methods, this study analyses the extent to which Article 8(5) contradicts the principles of a democratic rule of law, particularly due process of law, equality before the law, and institutional accountability. Several high-profile case studies involving prosecutors such as Pinangki Sirna Malasari and Urip Tri Gunawan illustrate the operational obstacles and legal stagnation created by this hierarchical authorization requirement. The study finds that the provision creates structural barriers to justice and fosters unequal treatment under the law. Reformulating Article 8(5) into a notification mechanism rather than a permission system would ensure a more balanced relationship between institutional protection and legal accountability. Significantly, this research contributes to the development of legal thought on prosecutorial reform by offering a normative framework that strengthens equality before the law and provides policy recommendations for enhancing transparency and accountability within Indonesia’s prosecution system.